Evolutionary and Integrative Analysis of Gibberellin-Dioxygenase Gene Family and Their Expression Profile in Three Rosaceae Genomes (F. vesca, P. mume, and P. avium) Under Phytohormone Stress - Sabir, Irfan Ali; Manzoor, Muhammad Aamir; Shah, Iftikhar Hussain; Abbas, Farhat; Liu, Xunju; Fiaz, Sajid; Shah, Adnan Noor; Jiu, Songtao; Wang, Jiyuan; Abdullah, Muhammad; Zhang, Caixi (Frontiers in Plant Science, 2022)
Gibberellin-dioxygenases (GAox) gene family plays a crucial role in regulating plant growth and development. GAoxs, which are encoded by many gene subfamilies, are extremely critical in regulating bioactive GA levels by catalyzing the subsequent stages in the biosynthesis process. Moreover, GAoxs are important enzymes in GA synthesis pathway and the GAox gene family has not yet been identified in Rosaceae species (Prunus avium L., F. vesca, and P. mume), especially in response to gibberellin and PCa (prohexadione calcium; reduce biologically active GAs). In the current investigation, 399 GAox members were identified in sweet cherry, Japanese apricot, and strawberry. Moreover, they were further classified into six (A-F) subgroups based on phylogeny. According to motif analysis and gene structure, the majority of the PavGAox genes have a remarkably well-maintained exon-intron and motif arrangement within the same subgroup which may lead to functional divergence. In the systematic investigation, PavGAox genes have several duplication events but segmental duplication that occurs frequently. A calculative analysis of orthologous gene pairs in Prunus avium L. among F. vesca, and P. mume revealed that GAox genes are subjected to purifying selection during the evolutionary process, resulting in functional divergence. The analysis of cis-regulatory elements in the upstream region of the 140 PavGAox members suggests a possible relationship between genes and specific functions of hormone response-related elements. Moreover, the PavGAox genes displayed a variety of tissue expression patterns in diverse tissues, with most of the PavGAox genes displaying tissue-specific expression patterns. Furthermore, most of the PavGAox genes expressed significant expression in bud under phytohormonal stresses. Phytohormones stress analysis demonstrated that some of PavGAox genes are responsible for maintaining the GA level in plant-like Pav co4017001.1 g010.1.br, Pav sc0000024.1 g340.1.br and Pav sc0000024.1 g270.1.mk. The subcellular localization of PavGAox protein utilizing a tobacco transient transformation system into the tobacco epidermal cells predicted that mostly GFP signal was found in the cytoplasm. These findings will contribute to a better understanding of the GAox gene family's interaction with prohexadione calcium and GA, as well as provide a strong framework for future functional characterization of GAox genes in sweet cherry.